ANALISIS PERMASALAHAN SIKAP PROFESIONALISME DALAM KINERJA GURU PADA SATUAN PENDIDIKAN - Fani Susanti; Afan Alfian Rizal; Dwi Erni Febrianti (Universitas Islam Malang, 2021)
This paper aims to determine the problem of professionalism in teacher performance in education units. This writing uses a descriptive qualitative approach where by looking for relevant and valid reading sources to collect accurate data as an effort to support this writing. Basically, many problems with professional attitudes arise because many teachers only master knowledge but do not master several other aspects. So that only teaching but ignoring the most important value in education itself. These problems arise due to lack of self-awareness in an educator. Professionalism is an aspect of expertise in the field being run. So that efforts to develop, improve, and self-evaluate educators must be pursued and must continue to be improved. Considering that educators are a central and main aspect in achieving educational goals. Teachers with good performance will produce human resources and outputs that will be of great benefit to the nation and country. Some of the problems in this matter are about professionalism towards legislation, professionalism towards colleagues, professionalism towards students, and professionalism towards superiors or leaders. Which will be analyzed in this writing to find out the big and small impact resulting from this.